(3GdSehW aj TQM GdeYdbGJ GdSHYs - (3CHh LYaQ CMeO Hf eMeO GdfMGS GdfMhis; (3YeQh Hf cdKhe Hf eGdc Hf YJGH, ef Hfj JZdH, CHh GdCShO,fMh (B40 (3b g`s
(3ChdgG (B:s
(3bGd CMeO Hf eMeO GdfMGS (B: (3GdPi LQi Ydjg CeQ CcKQ Cgd GddZI GdEcKGQ ai JaSjQ ZQjH GdTYQ s
(3BNQgG (B:s
(3JeJ GdbUjOI GdeNJGQI ef TYQ GdMGQK Hf MdRI hgj EMOi GdedMbJjf , hHGddg GdJhajb hHg CSJYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3cJHJ CHjGJ GdbUjOI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs